Development of a Soft Skills Competency Enrichment Book Model Focused on Hair Treatment Services - Hidayati, Esti; Basukiyatno, Basukiyatno; Agung N, Rahmad (Journal of English Language and Education, 2025)
This research aims to (1) identify relevant soft skills for students in hair treatment services at SMKN 1 Tegal, (2) design an effective enrichment book model to enhance students' soft skills, (3) compile an enrichment book that effectively improves soft skill competencies in hair treatment services, (4) analyze the feasibility and practicality of implementing the enrichment book in the learning process, and (5) determine its effectiveness in learning hair treatment services. This study employs Research and Development (RD) using the ADDIE model from Dick and Carey. Data collection techniques include questionnaires, interviews, observations, and documentation. The population consists of Class XII students of SMKN 1 Tegal, with two classes as samples, divided into control and experimental groups. Data analysis techniques involve normality tests, homogeneity tests, t-tests, and feasibility and effectiveness tests. The results indicate a positive and significant impact of the Soft Skills Competency Enrichment Book Model on students’ hair treatment skills. Teacher and student needs analysis includes student requirements, user analysis, and facility evaluation. Media development involves media and format selection, question compilation, and application design. Validation results show 93% for material and 94% for media aspects. Learning effectiveness is demonstrated by an increase in experimental class performance from 18% to 85%, proving the model's significant impact on enhancing students' hair treatment service skills.